Dimensi Tangible Dalam Pelayanan di Puskesmas Papakelas Kecamatan Tondano Timur - Margareth Rantung; Megalia Kaseger (Institut Pemerintahan Dalam Negeri, 2023)
This study aims to describe the Tangible Dimension in services at the Papakelan Health Center, East Tondano District. This study uses a descriptive qualitative approach, the number of informants is six people with data collection techniques namely observation, interviews, and documentation, with data analysis techniques through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the Tangible Dimensions of service at the Papakelan Health Center, East Tondano District, has not been fully running well because it is found that according to the research data, the services provided are still constrained by the lack of human resources, incomplete infrastructure and damaged to infrastructure, service procedures unknown to some patients, and the response of the public who are not satisfied with the services provided. For this reason, it is recommended to be able to propose additional human resources at the Puskesmas to the Health Office, complete infrastructure and repair damaged infrastructure, convey to each patient the outline of the service process at the Puskesmas, hear criticisms along with suggestions and input given by the community to improve services.